2020
DOI: 10.21873/invivo.12065
|View full text |Cite
|
Sign up to set email alerts
|

High Paip1 Expression as a Potential Prognostic Marker in Hepatocellular Carcinoma

Abstract: Background/Aim: Translation plays an important role in the carcinogenesis of various human tumors. Paip1 and eIF4A1 are translation-associated proteins that mediate the function of eukaryotic initiation factor 4F complex. This study aimed to analyse the relationship between the expression status of Paip1 and eIF4A1 and clinicopathologic features in hepatocellular carcinoma (HCC). Materials and Methods: Immunohistochemical analysis was used to evaluate the expression status of Paip1 and eIF4A1. Two pathologists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
3
5
1
Order By: Relevance
“…Indeed, we found a similar trend in the PAIP1 mRNA and protein level overexpression in oral cancers when compared to healthy controls (Fig. 1 ) 11 13 , 15 , 19 . Higher PAIP1 expression was a frequent event in cohorts of patients with OSCC, associated with higher risk and positive correlation with greater tumor size, LNM, and advanced stages of the tumor and reduced survival (Fig.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Indeed, we found a similar trend in the PAIP1 mRNA and protein level overexpression in oral cancers when compared to healthy controls (Fig. 1 ) 11 13 , 15 , 19 . Higher PAIP1 expression was a frequent event in cohorts of patients with OSCC, associated with higher risk and positive correlation with greater tumor size, LNM, and advanced stages of the tumor and reduced survival (Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Higher PAIP1 expression was a frequent event in cohorts of patients with OSCC, associated with higher risk and positive correlation with greater tumor size, LNM, and advanced stages of the tumor and reduced survival (Fig. 2 and Fig S3 ), consistent with that of various tumors 11 13 , 15 , 19 . Xie et al described similar findings in tongue carcinomas, but the representative data does not corroborate with the conclusion 20 .…”
Section: Discussionsupporting
confidence: 67%
“…Numerous studies have shown that PAIP1 was upregulated and was associated with the development of multifarious cancers. For example, Kim et al found that PAIP1 expression was elevated in hepatocellular carcinoma and high expression of PAIP1 was associated with tumor invasion and worse five-year overall survival (OS) [ 32 ]. Guan et al presented that PAIP1 was overexpressed in pancreatic cancer tissues, and depletion of PAIP1 signally lessened cell proliferation, metastasis and angiogenesis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of these studies indicated that PAIP1 is a potential prognostic biomarker for cancer. It is notable that PAIP1 is highly expressed in HCC tissues compared with the normal liver tissue, and the expression of PAIP1 in HCC tissues is significantly correlated with the prognosis of patients ( Kim et al, 2020 ). However, the roles and underlying molecular mechanism of PAIP1 in liver cancer are still unclear.…”
Section: Introductionmentioning
confidence: 99%